2016
DOI: 10.1016/j.jpainsymman.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Emotional Suffering in Palliative Care: Use of a Structured Note Template to Improve Documentation

Abstract: A structured note template with a prompt for emotional assessment increases the overall quantity and richness of documentation related to patient and family emotions. However, this documentation remains mostly descriptive. Additional prompting for documentation of recommendations to address identified emotional needs, and the use of screening tools for depression and anxiety, when appropriate, may be necessary for clinically meaningful quality improvements in patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Several studies have shown that a template can improve capture of data in documentation which improves qualities of documentation. 13,14 This QI project continues the theme that a template improves the quality of key components of documentation in family meetings within a critical care unit. 15 There may be additional education about key elements in a family meeting when physicians use the pro forma record.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown that a template can improve capture of data in documentation which improves qualities of documentation. 13,14 This QI project continues the theme that a template improves the quality of key components of documentation in family meetings within a critical care unit. 15 There may be additional education about key elements in a family meeting when physicians use the pro forma record.…”
Section: Discussionmentioning
confidence: 96%
“…Aggregative dashboards are but one of many tools for reducing EHR workload. Such solutions include note templates, such as that provided by Epic SmartPhrases (Epic Systems Corporation, Verona, Wisconsin, Unites States), 30,31 strategic menu design, 32,33 and order sets. 34 Automationcentric innovations also exist, such as automated problem list generation 35 and follow-up determination after radiographic testing, 36 as well as clinical decision support, alerts for risk stratification 37 and drug-disease interactions.…”
Section: Discussionmentioning
confidence: 99%
“…12 In fact, previous work has linked use of EMR in hospice with greater attention to key quality of care domains. 28,29 Additionally, structured and well-designed assessments yield more objective data and can be quicker to complete. We also believe it is essential that developers of hospice social work assessmentsdwhether electronic or paper-baseddshould obtain input from experienced social workers with knowledge of the unique complexities of the hospice setting.…”
Section: Discussionmentioning
confidence: 99%